Variables asociadas a la satisfacción del usuario externo del servicio de emergencia en el Hospital de EsSalud de Iquitos 2023 - Caballero Shavier, Elida Giannina (2024)
The objective of the research was to determine the variables associated with the satisfaction of the external user of the emergency service at the Hospital de Es Salud Iquitos 2023. The type of study was quantitative, with a non experimental, descriptive, correlational design. The population and sample were made up of 124 external users who accessed care in the emergency service of the Es Salud Iquitos hospital. The technique used was the survey and the instruments were: Data record sheet for external emergency users and Satisfaction Questionnaire for external users of the emergency service. Descriptive statistics were used to process the data and the non-parametric inferential statistics of free distribution called Chi Square (X2) were used for correlation analysis. Likewise, the SPSS statistical package version 24.0 was used to process the bivariate analysis. The results show that 43.5% were between 46 and 60 years old, 68.5% were women, 54% achieved a degree of higher technical education, and 66.9% received medical specialty care. Regarding the level of user satisfaction, 59.7% showed dissatisfaction with the care, while 40.3% showed satisfaction with the care received. An association was found between the level of satisfaction of the external user with: age (p=0.004), sex (p=0.024), level of education (p=0.038) and the specialty of care (p=0.027). In conclusion, there are variables statistically associated with the level of satisfaction of the external user in the emergency service of the Es Salud Hospital of Iquitos.